Phytotoxicity of common weeds on germination, seedling growth, NPK uptake and chlorophyll content of four hill crops of Garhwal Himalaya - Kejum Padu; Vinod Prasad Khanduri; Bhupendra Singh; Deepa Rawat; Manoj Kumar Riyal; Kewat Sanjay Kumar (Journal of Agriculture and Food Research, 2023)
The present investigation was undertaken to evaluate the allelopathic effects of three weed species i.e. Poa annua, Erigeron annuus and Stellaria media on seed germination, seedling growth, nutrient uptake and chlorophyll content of four agricultural crops, i.e. Hordeum vulgare, Triticum aestivum, Brassica juncea and Eleusine coracana. The different concentrations of weeds extracts were prepared to examine the allelopathic effects on agricultural crops. The results indicated inhibitory effects of different weeds extract on agricultural crops. Irrespective of the test crops, overall reduction in germination was recorded with the higher concentration (5%) of weeds extract prepared from Poa annua, Erigeron annuus and Stellaria media by 5.66, 17.55 and 18.86%, respectively. Similarly, growth was reduced by 11.65, 39.44, 42.75%, nutrients concentration by 31.22, 33.87, 15.87%, nutrient uptake by 37.65, 39.97, 31.15% and 31.97, 52.91, 63.74% in chlorophyll contents was observed with 5% extract of all three respective weeds. Less inhibitory effects were observed at lower concentrations in laboratory as well as in field conditions. The results also revealed that the allelopathic influences are species specific and the selected weeds have allelopathic potential in water-soluble extract, and their effect was dependent on their concentrations in water. The tolerance of crops was in the order of E. coracana > B. junicea > H. vulgare > T. aestivum. Among the weeds extract, the toxicity of the weeds was in the order of E. annuus > S. media > P. annua on all the test crops. The results of the present investigation suggest that the suitable weed management practices should be considered to minimize the loss of agricultural production due to allelopathic effects of weeds on crops so that the limited intractions between the agricultural crops and weeds is achieved for sustainable production of agricultural crops.